The agility challenge during organic growth - Pires, R.; Pereira, L.; Dias, Á.; Gonçalves, R.; Lopes da Costa, R.; Silva, R. V. da (International Journal of Learning and Intellectual Capital, 2023)
The growth of organizations naturally increases their complexity, often leading to a loss of agility which affects business performance. This research aims to study strategies for maintaining agility that keep up with the growth and consequent increase in complexity of organizations. This study was conducted with twenty-one interviews with consulting managers with the aim of knowing the main impacts, causes, and perceptions of organizational agility. The results showed that the main causes for the loss of agility are the non-prioritization of organizational problems and the lack of standardization and vagueness of processes, which has as main impacts the loss of efficiency, business, employee motivation and increased delivery time. To increase organizational agility the main findings, suggest critical actions to be taken: define and standardize processes, unify values and practices, and create coaching and training programs to consolidate concepts.